Goyim Gentiles and Israelites in Mishnah-Tosefta - Porton, Gary G. (Brown Judaic Studies, 2020)
This volume examines the way thatMishnah-Tosefta attempted to construct an Israelite ethnic identity in order to differentiate the Israelites from the gentiles who also populated the Land of Israel. This became an especially pertinent project with the destruction of the Jerusalem Temple, the failure of the Bar Kokhba Revolt, the increased influx of gentiles into the Land of Israel, and the social upheaval which resulted from the disruption of Israel's agricultural economy and the general economic decline experienced throughout the Roman world during that period. The organization of Mishnah-Tosefta indicates that their authors arranged their formulation of Israelite identity around a few key concepts/symbols: The Land of Israel, Israel's periods of Sacred Time, The People Israel and their Ethnic Institutions and Practices, The God of Israel, and The Residence of Israel's God.